Nanofluids for Automotive Radiators: A Review of Thermophysical Properties, Stability, Heat Transfer Performance, and Future Research Directions - Amogh Sambare (Journal of Applied Science and Advanced Engineering, 2026)
The persistent demand for compact, high-efficiency automotive cooling systems has driven significant research into nanofluids as next-generation coolants. This review critically examines recent advances in mono, hybrid, and ternary nanofluids applied to automotive radiators, synthesising over experimental and numerical studies published between during last decade. Key thermophysical properties such as thermal conductivity, dynamic viscosity, density, and specific heat capacity are discussed alongside the principal factors governing their variation with nanoparticle concentration, temperature, particle geometry, and base fluid composition. Nanofluid preparation methodologies (one-step and two-step) and strategies for stabilising colloidal dispersions such as including surfactant addition, ultrasonication, pH control, and zeta potential management are evaluated against practical longevity requirements. Empirical correlations for property estimation are tabulated and critically compared. Heat transfer performance data from radiator studies are synthesised, revealing that carbon-based nanofluids (graphene, MWCNTs) consistently outperform metal-oxide counterparts in thermal conductivity enhancement (up to 161.8%), while hybrid and ternary formulations demonstrate superior combined performance due to synergistic inter-particle effects. Practical challenges such as including erosion, clogging, agglomeration, and increased pumping power requirements are assessed with emphasis on long-term system reliability. The review concludes with a structured agenda for future research, highlighting the need for standardised testing protocols, machine-learning-assisted property prediction, and compatibility studies with modern radiator materials.